English Teachers’ Perceptions of Implementing the Deep Learning Approach in Elementary Schools - Jabbar, Nur Qohhari; Dewi, Puspa; Widodo, Sri (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
This study examines how elementary school English teachers perceive and implement the deep learning approach, revealing generally positive views toward its potential to enhance creativity, independence, and active student participation. Using a qualitative case study design, the study involved interviews with fourteen teachers from rural areas in the southern coast of Central Java and the Special Region of Yogyakarta. Thematic analysis identified three key findings: (1) teachers value deep learning for promoting mindful, meaningful, and joyful learning; (2) differences in teaching experience, institutional support, and access to training lead to varied levels of understanding and confidence; and (3) although most schools provide adequate resources, their use remains limited due to insufficient technical guidance. Deep learning emphasized in recent Indonesian curriculum reforms serves as an alternative to traditional rote-based practices, yet its classroom application remains inconsistent. The study concludes that clearer conceptual training, continuous professional development, and stronger school support systems are essential for ensuring more effective and consistent implementation of deep learning in elementary English teaching.